READING LITERACY STRATEGIES IN INDONESIAN LANGUAGE LEARNING FOR GRADE 10 STUDENTS OF STATE HIGH SCHOOL 13 JENEPONTO REGENCY - suhardi, Suhardi; Rahman Rahim, A; Syahruddin (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to describe the implementation of reading literacy strategies in Indonesian learning and identify supporting and inhibiting factors for its application in grade X students of SMA Negeri 13 Jeneponto Regency. The research uses a qualitative approach with a descriptive type of research. The research subjects consisted of class X Indonesian teachers and class X students who were selected purposively. Data were collected through observation techniques, semi-structured interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana interactive analysis model which included data reduction, data presentation, and conclusion drawn. The validity of the data was tested through triangulation of sources and techniques. The results of the study showed that the reading literacy strategy was implemented through reading activities 15 minutes before learning, the use of diverse and contextual texts, discussions on reading comprehension, and reflective assignments. The implementation of this strategy encourages increased student participation, the ability to understand the content of reading, and a positive attitude towards reading activities. Supporting factors for the implementation of the reading literacy strategy include teacher commitment, support for school literacy programs, and the availability of reading materials, while inhibiting factors include the low interest in reading of some students, limited learning time, and the influence of gadget use that has not been optimally controlled. This study concludes that reading literacy strategies have an important role in supporting Indonesian learning and need to be implemented sustainably with the support of various parties.